2015
DOI: 10.1039/c5dt00306g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterisation, and dehydrocoupling ability of zirconium complexes bearing hindered bis(amido)silyl ligands

Abstract: Herein we detail the synthesis and characterisation of a series of zirconium compounds featuring the bis(amido)silyl ligand [(i)Pr2Si(NDipp)2](2-) (Dipp = 2,6-diisopropylphenyl). The functionalisation of bis(amido)silyl zirconium halide complexes with a variety of nucleophiles, such as LiNMe2, LiBH4 and MeLi, was explored and the resulting products showed a propensity to form anionic zirconate salts when the syntheses were carried out in THF. One of the zirconate products, [(i)Pr2Si(NDipp)2]Zr(NMe2)2·ClLi(THF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…Despite computational evidence for a M II /M IV redox mechanism for amine borane dehydrogenation 212 , there is conflicting experimental evidence that indicates alternate mechanisms may also be involved. For example, several M IV precatalysts such as M(NMe 2 ) 4 (M = Ti, Zr) 208 , [ i Pr 2 Si(NDIPP) 2 ] Zr(NMe 2 ) 2 -LiCl(THF) 3 (DIPP = 2,6-diisopropylphenyl) 213 and K 5 -(Me 3 SiNCH 2 CH 2 ) 2 N(CH 2 CH 2 SiMe 2 CH 2 ) Zr (REF 196 ) may promote dehydrogenation via c-bond metathesis routes, while in other cases, M III metallocene species have been observed in situ 214 .…”
Section: Functionalization and Defunctionalizationmentioning
confidence: 99%
“…Despite computational evidence for a M II /M IV redox mechanism for amine borane dehydrogenation 212 , there is conflicting experimental evidence that indicates alternate mechanisms may also be involved. For example, several M IV precatalysts such as M(NMe 2 ) 4 (M = Ti, Zr) 208 , [ i Pr 2 Si(NDIPP) 2 ] Zr(NMe 2 ) 2 -LiCl(THF) 3 (DIPP = 2,6-diisopropylphenyl) 213 and K 5 -(Me 3 SiNCH 2 CH 2 ) 2 N(CH 2 CH 2 SiMe 2 CH 2 ) Zr (REF 196 ) may promote dehydrogenation via c-bond metathesis routes, while in other cases, M III metallocene species have been observed in situ 214 .…”
Section: Functionalization and Defunctionalizationmentioning
confidence: 99%
“…In particular, group 4 derivatives have been intensively investigated as highly active homogeneous amine–borane dehydrogenation catalysts. Most of these studies have been performed with metallocene-type sandwich complexes [M­(η 5 -C 5 R 5 ) 2 X n ] with the group 4 metal centers in the +2, +3, and +4 oxidation state, but homoleptic amido compounds [M­(NMe 2 ) 4 ] (M = Ti, Zr) and other zirconium nonmetallocene derivatives were also active toward secondary and primary amine–boranes. , To isolate key intermediates and to gain mechanistic insight into the catalytic dehydrogenation of amine–boranes several research groups have studied the stoichiometric version of these reactions. In s-block and early transition-metal systems, the first stage of the reaction appears to involve the formation of amidoborane complexes via N–H bond activation. ,,, The amidoborane NR 2 BH 3 ligands bound to the metal centers exhibit M–N and M···H–B interactions, and subsequent hydride transfer from boron to the metal results in aminoboranes (NR 2 BH 2 ) n and metal hydride species.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these studies have been performed with metallocene-type sandwich complexes [M(η 5 -C 5 R 5 ) 2 X n ] with the group 4 metal centers in the +2, +3, and +4 oxidation state, 5−14 but homoleptic amido compounds [M-(NMe 2 ) 4 ] (M = Ti, Zr) 14 and other zirconium nonmetallocene derivatives were also active toward secondary and primary amine−boranes. 15,16 To isolate key intermediates and to gain mechanistic insight into the catalytic dehydrogenation of amine−boranes several research groups have studied the stoichiometric version of these reactions. In s-block and early transition-metal systems, the first stage of the reaction appears to involve the formation of amidoborane complexes via N−H bond activation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Further to this, it is observed that 2 is a highly efficient catalyst for the dehydrocoupling of Me 2 NH·BH 3 and, in fact, possesses the highest TOF (turnover frequency) of any group 4 catalyst (>600 h –1 ), the previous highest being the Zr-amide species ([NSiN] Dipp Zr­(NMe 2 ) 2 (μ-Cl)­Li­(THF) 3 ) reported by Rivard et al (TOF = 420 h –1 ) . Decreasing the steric bulk present in compound 2 down to the single t Bu group, offered in compound 3, leads to a decrease in TOF.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that treatment of Me2NH•BH3 with 10 mol% [Cp*2ZrOMes][B(C6F5)4] // PR3 (R = t Bu (7), Cy (8), Et (9), Ph (10), Mes (11), C6F5 (12)) in PhCl (25 °C) led to a sluggish reaction resulting in < 5% conversion to [Me2N-BH2]2 over 24 h in all cases, as calculated by 11 B NMR spectroscopy, and when R = Ph, Mes and C6F5 no conversion was observed. Changing the ancillary ligands on Zr from Cp* (pentamethylcyclopentadienyl) to Cp (14)(15)(16)(17)(18)(19) led to a marked improvement in the reactivity, as shown in Figure 4. This is consistent with previous observations, where intramolecular Zr/P FLPs, bearing Cp ancillary ligands, give significantly more rapid reactivity when compared to their Cp* cousins.…”
Section: Dehydrocoupling Of Me2nh•bh3 Using Intermolecular Flpsmentioning
confidence: 97%